2023
DOI: 10.30935/cedtech/12721
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing reading capability of young Thai students with augmented reality technology: Design-based research

Abstract: The Thai language, which is part of the Indo-Iranian language family, carries on rituals and local knowledge that have been passed down from generation to generation. The Thai National Statistics Office found that 10% of elementary school students in Thailand cannot read. This means that 90% of elementary school students in Thailand can read. The numbers disagree with a report from an international assessment agency that said young Thai students’ reading skills were the 50<sup>th</sup> best out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Their results showed that reading activities carried out with AR storybooks support students' reading comprehension performance by providing an interactive reading experience. There are also different studies showing that AR storybooks support reading comprehension performance (Bursalı & Yılmaz, 2019;Danaei et al, 2020;Nasongkhla & Sujiva, 2023). On the other hand, it is concluded that AR storybooks do not have an effect on the level of simple comprehension (Şimşek & Direkci, 2023).…”
Section: Augmented Reality Storybooks and Reading Comprehensionmentioning
confidence: 97%
“…Their results showed that reading activities carried out with AR storybooks support students' reading comprehension performance by providing an interactive reading experience. There are also different studies showing that AR storybooks support reading comprehension performance (Bursalı & Yılmaz, 2019;Danaei et al, 2020;Nasongkhla & Sujiva, 2023). On the other hand, it is concluded that AR storybooks do not have an effect on the level of simple comprehension (Şimşek & Direkci, 2023).…”
Section: Augmented Reality Storybooks and Reading Comprehensionmentioning
confidence: 97%
“…The conception of the metaverse [1], which postulates a virtual environment that enables interaction between physical and digital constituents [2], has taken tangible form, owing to the proliferation of virtual reality (VR) and augmented reality (AR) technologies [3]. This transcendent paradigm shift in human-digital interaction has piqued the interest of technologists and futurists alike [4], extending its tendrils into a broad array of online environments.…”
Section: Introductionmentioning
confidence: 99%